Comparing the Effect of Electronic and Lecture Education on the Knowledge of Sedation in Cardiac Intensive Care Unit Nurses - Ghadimi, Maryam; Haddadi, Rana; Chaibakhsh, Yasmin; zia Totonchi, Mohammad; Khaleghparast, Shiva; Sheikh Fathollahi, Mahmood; Shahidifar, Samaneh; Shamseh, Mahnaz (Journal of Neonatal Surgery, 2025)
Introduction: Evaluate the lecture-based and e-education on the increasing knowledge of nurses in ICU in terms administration of sedative drugs. Methods: in quasi-experimental 60 cardiovascular ICU nurses were randomly divided into two groups, receiving in-person training and electronic training through 2 hours sessions for two weeks. Data then were collected before, 1 week, 2 weeks, and 1 month after training using a medication information questionnaire and evaluated with statistical analysis. Results: The positive effect of the educational intervention one week and two months after intervention (p<0.001) either in an in-person or e-learning group was observed. A significant reduction in the knowledge level of the two groups was observed two months after education(p<0.001). However, the knowledge of the two groups were at a higher level than before the intervention (p< 0.001). Conclusion: E-learning methods can be an alternative to teaching and retraining pharmacology topics in the traditional way for nurses.